ANALISIS FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA NOMOR 112/DSN-MUI/IX/2017 TERHADAP PRAKTIK SEWA MENYEWA BUS DI PERUSAHAAN OTOBUS ACM MAHADAT - Mahadat, Anwar; Chaniago, Asdi; Misno (Institut Agama Islam Sahid Bogor, 2024)
This study aims to analyze the practice of leasing at the Otobus Company ACM Mahadat Bogor. This company claims to make Islamic sharia as a guideline in its management. How is the leasing practice actually carried out when viewed from the DSN-MUI fatwa? The research method used is normative-qualitative, where data is obtained through observation, interviews and document studies. The analysis uses the Fatwa of the National Sharia Council of the Indonesian Ulema Council Number 112/DSN-MUI/IX/2017. The results of this study indicate that the practice of leasing carried out by PO ACM Mahadat is in accordance with the DSN-MUI fatwa. The contract used is an ijarah (leasing) contract in which the company rents out buses to transport passengers with compensation in accordance with the mutual agreement. There are a number of things that need to be corrected from the practice that has been carried out, namely related to the down payment which should not be completely forfeited when an agreement occurs and the replacement of other buses that are not in accordance with the initial agreement if there is a disruption to the bus that has been ordered. Overall, the bus leasing contract at the Otobus Company ACM Mahadat is in accordance with sharia with the ijarah contract as the type of contract being implemented.